QPrimerDB: a thermodynamics-based gene-specific qPCR primer database for 147 organisms. Issue Volume 46:Issue D1(2018) (21st August 2017) - Lu, Kun; Li, Tian; He, Jian; Chang, Wei; Zhang, Rui; Liu, Miao; Yu, Mengna; Fan, Yonghai; Ma, Jinqi; Sun, Wei; Qu, Cunmin; Liu, Liezhao; et al.
Abstract: Real-time quantitative polymerase chain reaction (qPCR) is one of the most important methods for analyzing the expression patterns of target genes. However, successful qPCR experiments rely heavily on the use of high-quality primers. Various qPCR primer databases have been developed to address this issue, but these databases target only a few important organisms. Here, we developed the qPrimerDB database, founded on an automatic gene-specific qPCR primer design and thermodynamics-based validation workflow. The qPrimerDB database is the most comprehensive qPCR primer database available to date, with a web front-end providing gene-specific and pre-computed primer pairs across 147 important organisms, including human, mouse, zebrafish, yeast, thale cress, rice and maize. In this database, we provide 3331426 of the best primer pairs for each gene, based on primer pair coverage, as well as 47760359 alternative gene-specific primer pairs, which can be conveniently batch downloaded. The specificity and efficiency was validated for qPCR primer pairs for 66 randomly selected genes, in six different organisms, through qPCR assays and gel electrophoresis. The qPrimerDB database represents a valuable, timesaving resource for gene expression analysis. This resource, which will be routinely updated, is publically accessible at http://biodb.swu.edu.cn/qprimerdb .